A 16-yr photometric campaign on the eclipsing novalike variable DW Ursae Majoris. Issue 3 (22nd December 2016) - Boyd, D. R. S.; de Miguel, E.; Patterson, J.; Wood, M. A.; Barrett, D.; Boardman, J.; Brettman, O.; Cejudo, D.; Collins, D.; Cook, L. M.; Cook, M. J.; Foote, J. L.; et al.
Abstract: We present an analysis of photometric observations of the eclipsing novalike variable DW UMa made by the CBA consortium between 1999 and 2015. Analysis of 372 new and 260 previously published eclipse timings reveals a 13.6 yr period or quasi-period in the times of minimum light. The seasonal light curves show a complex spectrum of periodic signals: both positive and negative 'superhumps', likely arising from a prograde apsidal precession and a retrograde nodal precession of the accretion disc. These signals appear most prominently and famously as sidebands of the orbital frequency; but the precession frequencies themselves, at 0.40 and 0.22 cycles per day, are also seen directly in the power spectrum. The superhumps are sometimes seen together, and sometimes separately. The depth, width and skew of eclipses are all modulated in phase with both nodal and apsidal precession of the tilted and eccentric accretion disc. The superhumps, or more correctly the precessional motions that produce them, may be essential to understanding the mysterious 'SW Sextantis' syndrome. Disc wobble and eccentricity can both produce Doppler signatures inconsistent with the true dynamical motions in the binary, and disc wobble might boost the mass-transfer rate by enabling the hot white dwarf to directly irradiate the secondary star.